The influence of globalization processes in society on the content of training professionally mobile skilled workers - Сушенцева, Лілія (Pedagogy of Higher and Secondary Education, 2014)
Sushentseva L. L. The influence of globalization processes in society on the content of training professionally mobile skilled workers. The article covers topical issues concerning the influence of globalization processes in society on choosing and structuring the content of training future professionally mobile skilled workers. The author highlights the essence of globalization and its political, economic, cultural and social aspects. The author also substantiates the growing interest in forming professional mobility of future skilled workers in the context of globalization changes in society and appearing a labour-marke